Removal of Methylene Blue by Adsorption onto Activated Carbon From Coconut Shell (Cocous Nucifera L.) - Khuluk, Rifki Husnul; Rahmat, Ali; Buhani, Buhani; Suharso, Suharso (Indonesian Journal of Science and Technology, 2019)
This research has been conducted on process of production activated carbon from coconut shells, which are activated both physics and chemistry to improve the adsorption of methylene blue. The process of physical activation was done by burning the coconut shell using a furnace at a temperature of 700Â°C. The chemical activation was done using H3PO4 activator. The result of activated carbon physical activation (CAP) has a greater absorbency than activated carbon chemical activation (CAC) with each of the absorption of methylene blue at 99.42 and 98.64%. Analysis of surface morphology on the adsorbent was performed using a Scanning Electron Microscope (SEM). SEM results indicated that (CAP) has a surface morphology that is relatively similar to commercial activated carbon (CACm). Adsorption test was conducted on the determination of the optimum pH, adsorption rate, and isotherm adsorption of methylene blue. The results of the optimum pH on CAC, CAP, and CACm respectively obtained at pH 8 and the optimum contact time is obtained respectively at 40, 60, and 80 minutes. Adsorption kinetics data of methylene blue on CACm, CAP, and CAC tend to follow the pseudo second order kinetics with a correlation coefficient (R2) is 0.937; 0.950; and 0.999, respectively. Adsorption isotherm of methylene blue on CACm, CAP, and CAC tend to follow the model of Freundlich isotherms.